PENGARUH KELUARGA BERENCANA TERHADAP PEMBERDAYAAN PEREMPUAN DI NUSA TENGGARA BARAT - Lalu Fathurrahman (Valid: Jurnal Ilmiah, 2016)
Empowerment emphasizes the participation, so they need to participate fully in decisionmaking processes of their lives. Participation of family planning is one of the factors that influence women's empowerment. This research aims to study the influence of the participation of family planning to women's empowerment in West Nusa Tenggara (NTB) by using the results SDKI 2007. The unit of analysis is the married women between the ages of 15-49 years who had at least one child born alive. The independent variables are: participation of family planning, Age At First Marriage, Level of Education, Employment Status, Number of Children Ideal, and the Cohort mother. Meanwhile, the independent variable is the Women's Empowerment using Binary Logistic analysis. Participation of family planning are factors that have a significant influence on the empowerment of women in the province, women who use contraceptives have a higher tendency to experience empowerment than those not using contraception. On the other hand, a variable level of education appears to have a significant influence on the chances of women experience empowerment. It is clear that education remains a factor affecting the empowerment of women. Thus the probability of occurrence of empowerment is higher in women who use contraception and highly educated (high school and above). While other variables such as age at first marriage, employment status, the ideal number of children and birth cohorts sinifikan not affect the empowerment of women. This may be because there are other factors that have a stronger influence on women's empowerment